Long-Term Survival and Liver-Related Events after Pegylated Interferon/Ribavirin Therapy in HIV-Infected Patients with Chronic Hepatitis C. Issue 1 (January 2015) - Labarga, Pablo; Fernández-Montero, José V; de Mendoza, Carmen; Barreiro, Pablo; Soriano, Vincent
Background: Sustained HCV clearance after hepatitis C therapy is associated with reduced liver-related complications and death. It is unknown if treatment may provide any clinical benefit in patients that fail therapy. This could be particularly relevant in HIV–HCV-coinfected patients, in whom liver disease progresses more rapidly. Methods: This was a retrospective study of clinical end points in a large cohort of HIV–HCV-coinfected patients with compensated liver disease followed since 2004. Patients were stratified into three groups: treated and cured, treatment failures and non-treated. Follow-up ended at the time of last visit, first liver decompensation event or death. Results: A total of 527 HIV–HCV-coinfected patients were examined, of whom 339 (64.3%) had been treated with pegylated interferon/ribavirin. During a mean follow-up of 70.5 months, hepatic decompensation events or liver-related deaths occurred less frequently in cured patients (4/138; 2.9%) than in treatment failures (28/201; 13.9%) or untreated (25/188; 13.3%) patients ( P <0.001). Interestingly, in the subset of patients with baseline advanced liver fibrosis (Metavir F3–F4), those with treatment failure experienced less hepatic decompensation events or deaths than untreated patients (19% versus 42%; P =0.005) and this finding was more pronounced in patients harbouring IL28B-CC alleles (15.8% versus 47.4%; P =0.02). Conclusions: Sustained HCV clearance following pegylated interferon/ribavirin therapy is associated with a reduced incidence of liver complications and death in HIV–HCV-coinfected patients. In the subset of patients with baseline advanced liver fibrosis, treatment provides clinical benefit despite lack of sustained virological response. The transient antiviral and/or anti-inflammatory effect of interferon, more recognizable in IL28B-CC carriers, could explain this finding.